SOCIO-ECONOMIC AND ABRATION STUDY IN RANGSANG ISLAND, MERANTI REGENCY - Meyzi Heriyanto; Indra Safri; M. Yazid Fauzi (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study discusses the socio-economic status of the people of Rangsang Island, Meranti Islands Regency, Riau Province. The discussion in this study is focused on the District of Rangsang Pesisir. The factors that become the focus of writing are economic and social including changes in social values, livelihoods and people's incomes. The method used is descriptive quantitative method by analyzing primary data and secondary data. The analysis results show that abrasion causes social values to change and affects people's livelihoods